2020
DOI: 10.1111/1744-7917.12787
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal feeding as a potential mechanism of osmoregulation in aphids

Abstract: Diurnal variation in phloem sap composition has a strong influence on aphid performance. The sugar-rich phloem sap serves as the sole diet for aphids and a suite of physiological mechanisms and behaviors allow them to tolerate the high osmotic stress. Here, we tested the hypothesis that night-time feeding by aphids is a behavior that takes advantage of the low sugar diet in the night to compensate for osmotic stress incurred while feeding on high sugar diet during the day. Using the electrical penetration grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The boxplot displays the median as a horizontal line, the interquartile range as a box, the maximum and minimum values as bars or 'whiskers', and outliers are indicated with dots. Nachappa et al, 2016;Pineda et al, 2016), and the mechanisms commonly attributed are reduced turgor pressure and increased viscosity negatively affecting phloem access, ingestion rate, or osmoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The boxplot displays the median as a horizontal line, the interquartile range as a box, the maximum and minimum values as bars or 'whiskers', and outliers are indicated with dots. Nachappa et al, 2016;Pineda et al, 2016), and the mechanisms commonly attributed are reduced turgor pressure and increased viscosity negatively affecting phloem access, ingestion rate, or osmoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…On poorer quality hosts, aphids show an increase in the number of cell probes and the duration of salivation (Ponder et al, 2001), indicating difficulty in establishing sustained feeding sites. However, studies evaluating phloem feeding behaviour in response to water limitation have found mixed results, with some studies documenting a reduction in the time spent feeding from phloem on water-limited hosts (Guo et al, 2016) and some studies finding no difference in feeding (Ponder et al, 2001;Hale et al, 2003;Nachappa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aphid stylet passage, saliva excretion and food ingestion in the host tissues cannot be directly investigated, but these activities can be monitored with application of the electrical penetration graph (EPG) technique. This approach is widely used to assess the probing and ingestion behavior of the aphids [ 42 , 43 , 44 , 45 , 46 ]. Analysis of the several parameters derived from the EPG recordings (e.g., frequency, duration and sequence of different waveforms) enables in-depth assessment of behavioral responses of the aphids to the host plant tissues [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no significant difference between RTC-406 and RTC-144 in the phloem phase. Aphids are phloem feeders that occasionally feed on xylem fluid (Nalam et al, 2020), possibly to attenuate the high osmotic potential of the phloem sap (Douglas, 2006;Tetreault et al, 2019). The EPG results expose that aphids spent more Gene expression patterns were sorted into up-and down-regulated genes upon 6, 24, and 96 h of aphid feeding on RTC-144 tef plants.…”
Section: Non-granular Trichome Density Is Negatively Correlated With mentioning
confidence: 99%